Strengthening Modern Policing Strategies for Public Safety and Crime Reduction - Tri Widada (Universitas Negeri Semarang, 2025)
Modern policing faces increasing challenges due to evolving crime patterns, rapid urbanization, and heightened public expectations regarding security and law-enforcement performance. This study investigates the effectiveness of contemporary policing strategies—particularly community policing, problem-oriented policing, patrol optimization, and crime-mapping analytics—in enhancing public safety and reducing crime rates. Using a mixed-methods approach, this research analyzes five years of crime data from metropolitan regions, evaluates patrol deployment structures, and conducts field interviews with officers, community leaders, and municipal administrators. Results demonstrate that integrated policing models combining proactive patrols, community engagement, and evidence-based crime analysis contribute significantly to property-crime reduction, faster response times, and improved citizen trust. Additionally, the adoption of structured problem-solving frameworks helps police departments identify underlying causes of disorder rather than responding solely to symptoms. However, the study also identifies persistent barriers including resource constraints, uneven officer training, and limited inter-agency data integration. This research contributes to the growing body of policing literature by offering a comprehensive evaluation of multi-layered policing approaches and proposing operational recommendations for enhancing law-enforcement effectiveness and community collaboration.